Results From Australia's 2016 Report Card on Physical Activity for Children and Youth - Schranz, Natasha K; Olds, Timothy; Boyd, Roslyn; Evans, John; Gomersall, Sjaan R; Hardy, Louise; Hesketh, Kylie D; Lubans, David R; Ridgers, Nicola D; Straker, Leon; Vella, Stewart; Ziviani, Jenny; et al. (My University, 2016)
Background: Two years on from the inaugural Active Healthy Kids Australia (AHKA) Physical Activity Report Card, there has been little to no change with the majority of Australian children still insufficiently active. Methods: The 2016 AHKA Report Card was developed using the best available national- and state-based physical activity data, which were evaluated by the AHKA Research Working Group using predetermined weighting criteria and benchmarks to assign letter grades to the 12 Report Card indicators. Results: In comparison with 2014, Overall Physical Activity Levels was again assigned a D- with Organized Sport and Physical Activity Participation increasing to a B (was B-) and Active Transport declining to a C- (was C). The settings and sources of influence again performed well (A- to a C+), however Government Strategies and Investments saw a decline (C+ to a D). The traits associated with physical activity were also graded poorly (C- to a D). Conclusions: Australian youth are insufficiently active and engage in high levels of screen-based sedentary behaviors. While a range of support structures exist, Australia lacks an overarching National Physical Activity Plan that would unify the country and encourage the cultural shift needed to face the inactivity crisis head on.
Journal of Physical Activity and Health
Keywords: public health; sedentary behavior; Adolescents and youth; Childhood and child development; Health and wellbeing